Professional service conglomerates and jurisdictional competition: Influences of digital technologies and regulations - Köktener, Berker (Graduate School, 2022)
This study focuses primarily on phenomena in the broader perspective of the accounting firms' evolution and the role of digitalization and regulations. Accounting firms may grow their size and variety of services over time and evolve from a Professional Service Firm (PSF) into a Professional Service Conglomerate (PSC). Despite their fundamental differences, various professional groups remain in a single organization during this change. How does a PSF transform into a PSC, and what keeps distinct professional groups together? While there is a vast literature on PSFs, the research on PSCs is limited and fragmented. Also the studies are limited in explaining how digitalization plays a role in the transformation of professions and PSCs. The study has identified three research streams emphasizing different themes: the role of the broader institutional environment, the results of the changing market conditions, and the purposeful strategic actions in becoming a PSC. The research has empirically analyzed a major accounting firm's historical transformation to a PSC over 40 years in an emerging country. The results have noted the critical roles of a particular country's business system and institutional changes in the PSC's organizational context. These factors, such as digitalization and regulatory changes, directly affect the demand for various professional services and their supply, leading to changes in the firm's partnership structure and disciplinary characteristics. In this regard, the contributions to the literature are threefold. First, the study provides a model describing how PSFs transform into PSCs, based on a comprehensive account of how the institutional environment has impacted the focal PSC. Secondly, the study outlines what keeps distinct professional groups inside the organizational boundaries instead of establishing independent professional firms, bringing additional insights to the literature on organizational boundaries. Thirdly, the study develops and analyzes a case study of a leading PSF's transformation into a PSC over 40 years in an emerging country. Lastly, the study calls for further research on the growth and internal organizing factors of PSFs, especially in understudied environments. In the following section, the study zooms into inter-professional dynamics between established and new professions under digitalization and regulatory changes. Internal tensions arise from disparities amongst the professions that comprise multidisciplinary professional service firms. Prior work has advanced our understanding of how the institutional context intersects professional boundaries and creates jurisdictional conflicts in multi-occupational settings. However, we know little about how regulatory changes impact inter-professional and intra-organizational dynamics between established and new professions at professional service firms. Besides, multi-professional service firms must deal with external pressures, such as increasing digitalization. Advances in digital technologies affect the content and control of work among professions, reshaping established jurisdictions. The importance of digital technologies is growing for professionals and their organizations. However, there is limited understanding of how this trend affects professions' content and jurisdictional arrangements. The study explored changes in audit work due to digitalization and how auditors responded to jurisdictional conflicts through boundary work. It analyzed data collected from semi-structured interviews, participant observations, and archival data in a Big Four firm. The findings indicate that new regulations have radical impacts on established jurisdictions. The findings also show that digitalization impacts auditors' critical activities and jurisdictions in the diagnosis and treatment phases, increasing the effectiveness and value of audit work. Accounting auditors can respond to jurisdictional conflicts through different boundary work types for each professional practice act. The study advances our understanding of digitalization's implications on professions. It argues that professions can reduce contestation and increase collaboration through boundary work in the diagnosis and treatment phases. In contrast, professionals' ability to abstract helps them maintain favorable conditions in the inference phase. Later, the study zooms out and connects the findings with the ongoing debate about how advances in intelligent technologies affect professions and their work. The central argument is about whether such changes will make humans more productive and professions accessible to society or make them obsolete. Current views have two opposing camps. Technology replaces most jobs resulting in long-term technological unemployment, or some jobs resulting in short-term technological unemployment. It will bring prosperity by reskilling labor and creating new jobs in the long term. The study structures the fragmented contributions of prior work by analyzing the implications of technological change through the theoretical lenses of the literature on professions. By bridging the technology and professions literature, the study organizes the critical dimensions to link the previously unconnected concepts and structure current contributions in a novel way. In this manner, the study introduces a theoretical approach that allows studying the implications of technology on professions. Besides, the study argues that technological change will replace professions, create new professions, improve productivity, or make them obsolete. However, it depends on how it affects specific acts of professional practices. Lastly, the study offers directions for future research based on the propositions developed.
Profesyonel hizmet konglomeraları ve yetki alanı rekabeti: Dijital teknolojiler ve düzenlemelerin etkileri
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: digital technologies; dijital teknolojiler; account ing firms; muhasebe firmaları; professional service firms; profesyonel hizmet firmaları